Perception of educational actors about the use of mobile devices: A case study - Maldonado, Verónica (2020)
The implementation of innovative methodologies related to the use of digital resources has allowed a relevant participation of educational communities. This article provides the views of the students and teachers of an educational institution benefiting from the Mobile Digital Classroom Project executed by Fundación Telefónica, part of the Profuturo Project and articulated with the Ministry of Education of Ecuador. The research aims to determine the perception of teachers and students in relation to the educational use of mobile devices. The inductive method was used, thus, the starting point was the data provided by the 70 children of school age and 10 teachers to perform the construction of the categories. 75% of the participants of this research associate the use of the mobile device with learning, also referring to the learning acquired in a fun way. In addition, they mention that the tablet allows them to access information, to know other cultures, to enable research, which generates significant learning. The mobile device within the classroom achieved positive results in the learning processes, all participants perceive and value the resource as positive, they assume it as a bridge that brings them closer to the knowledge of other cultures, gives them the possibility to investigate, to learn values, content of topics and access to reading.